Polymer-ritonavir derivate nanomedicine with pH-sensitive activation possesses potent anti-tumor activity in vivo via inhibition of proteasome and STAT3 signaling - Sivák, Ladislav; Šubr, Vladimír; Kovářová, Jiřina; Dvořáková, Barbora; Šírová, Milada; Říhová, Blanka; Randárová, Eva; Kraus, Michal; Tomala, Jakub; Studenovský, Martin; Vondráčková, Michaela; Sedláček, Radislav; et al. (Journal of controlled release, 2021)
Drug repurposing is a promising strategy for identifying new applications for approved drugs. Here, we describe a polymer biomaterial composed of the antiretroviral drug ritonavir derivative (5-methyl-4-oxohexanoic acid ritonavir ester; RD), covalently bound to HPMA copolymer carrier via a pH-sensitive hydrazone bond (P-RD). Apart from being more potent inhibitor of P-glycoprotein in comparison to ritonavir, we found RD to have considerable cytostatic activity in six mice (IC50 ~ 2.3-17.4 μM) and six human (IC50 ~ 4.3-8.7 μM) cancer cell lines, and that RD inhibits the migration and invasiveness of cancer cells in vitro. Importantly, RD inhibits STAT3 phosphorylation in CT26 cells in vitro and in vivo, and expression of the NF-κB p65 subunit, Bcl-2 and Mcl-1 in vitro. RD also dampens chymotrypsin-like and trypsin-like proteasome activity and induces ER stress as documented by induction of PERK phosphorylation and expression of ATF4 and CHOP. P-RD nanomedicine showed powerful antitumor activity in CT26 and B16F10 tumor-bearing mice, which, moreover, synergized with IL-2-based immunotherapy. P-RD proved very promising therapeutic activity also in human FaDu xenografts and negligible toxicity predetermining these nanomedicines as side-effect free nanosystem. The therapeutic potential could be highly increased using the fine-tuned combination with other drugs, i.e. doxorubicin, attached to the same polymer system. Finally, we summarize that described polymer nanomedicines fulfilled all the requirements as potential candidates for deep preclinical investigation.
Keywords: Animals; Doxorubicin; Nanomedicine; Cell Line, Tumor; Hydrogen-Ion Concentration; nádorové buněčné linie; Polymers; Antineoplastic Agents; Mice; protinádorové látky; myši; proteasomový endopeptidasový komplex; nanomedicína; ritonavir; doxorubicin; polymery; zvířata; Ritonavir; koncentrace vodíkových iontů; Proteasome Endopeptidase Complex